Rethinking the Match: A Proposal for Modern Matchmaking. (January 2018) - Ray, Chris; Bishop, Steven E.; Dow, Alan W.
Abstract : Since the 1950s, the National Resident Matching Program, or "the Match, " has governed the placement of medical students into residencies. The Match was created to protect students in an era when residency positions outnumbered applicants and hospitals pressured students early in their academic careers to commit to a residency position. Now, however, applicants outnumber positions, applicants are applying to increasing numbers of programs, and the costs of the Match for applicants and programs are high. Meanwhile, medical education is evolving toward a competency-based approach, a U.S. physician shortage is predicted, and some researchers describe a "July effect"—worse clinical outcomes correlated with the mass entry of new residents. Against this background, the authors argue for adopting a more modern, free-market approach to residency matchmaking that might better suit the needs of applicants, programs, and the public. They propose allowing students who have been identified by their medical schools as having achieved graduation-level competency to apply to residency programs at any point during the year. Residency programs would set their own application timetables and extend offers in an ongoing fashion. Students, counseled by their schools, would accept or decline offers as desired. The authors argue this approach would better support competency-based education while allowing applicants and programs more choice regarding how they engage and adapt within the selection process. The approach's staggered start times for new residents might attenuate the July effect and improve outcomes for patients. Medical students might also enter and thereby complete residency earlier, increasing the physician workforce.